THE INFLUENCE OF JOB STRESS AND JOB STATISFACTION ON EMPLOYEE’S ORGANIZATIONAL COMMITMENT AT CV. DIPO PRODUCTION - Paramita, Widya; Putra, Toni Eka; Handaru, Agung Wahyu (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
The purpose of this research are: 1) To find a description of the job stress, job satisfaction and organizational commitmentatCV. Dipo Production, 2) To determine whether there isan influence ofjob stress on employee’s organizational commitment at CV. Dipo Production, 3) To determine whether there is aninfluence of job statisfaction on employee’s organizational commitment at CV. Dipo Production, 4) To determine whether there isinfluence of job stress and job statisfaction simultaneously on employee’s organizational commitment at CV. Dipo Production. The sample of this research are all employees who work as a Tour Leader at CV. Dipo Production.Research data retrieval by survey method with questionnaires and the data processed with SPSS version 22.This research using descriptive and explanatory analysis. The Results of regression showed that job stress has a negative and significant effect on organizational commitment. While job statisfaction has a positive and significant effect on organizational commitment. Keywords: Job Stress, Job Statisfaction, Organizational Commitment